PERILAKU YANG MENDORONG KEBERHASILAN ASI EKSKLUSIF PADA WANITA BEKERJA DI FAKULTAS KEDOKTERAN UNIVERSITAS GADJAH MADA: STUDI POSITIVE DEVIANCE - , WURI KATHLEEN HERNINGSIH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: One of the factors that triggers failure of exclusive breastfeeding is the status as a working mother. Positive deviance is a method to find solution and strategy of working mothers to overcome difficulty in giving exclusive breastfeeding during working time. As one of the health institution that wants to solve local, national, and global problem, study about positive deviance among working mothers in FK UGM in giving exclusive breastfeeding had never been done. Goal: To find solutions and strategies from working mothers in FK UGM in overcoming the difficulties of implementation of exclusive breastfeeding during working time. Method: This research is a qualitative-based research on 11 female staff of FK UGM that has successfully performing exclusive breastfeeding in the last two years. Data is achieved by doing in-depth interviews with the respondent. Validation of the data conducted with triangulation method and documentations. Results: Even though busy with work, exclusive breastfeeding is given because working mothers understand the benefits of breastfeeding for the baby. Mother's milk is given by squeezing mother's milk at the work place or breastfeeding the baby directly at break time. FK UGM hasn't providing facility that supports exclusive breastfeeding with consequence the working mothers still giving exclusive breastfeeding with existing facility. To cope with work stress, stress management is needed so that breast milk production wonât be inhibited. Support from husband, family and working partner is also giving influence in the successfulness of exclusive breastfeeding while working. Providing lactation room, daycare, and tolerance in working time are the things that can be provided to facilitate exclusive breastfeeding for working mothers. Conclusion: Solutions for working mothers to still exclusively breastfed are by applying stress management so that work stress wonât interfere with breast milk production and utilizing existing facilities. The strategy is to do with expressing milk or breastfeeding during break time and eat nutritious foods. The success of this strategy and solutions is backed by the will and knowledge of the importance of breastfeeding mothers and the support of her husband, family, and coworkers.